2020
DOI: 10.1007/s00701-020-04223-x
|View full text |Cite
|
Sign up to set email alerts
|

5-ALA fluorescence in a WHO grade I papillary glioneuronal tumour: a case report

Abstract: Abstract5-ALA is proven to be effective in high-grade glioma operative resection. The use of 5-ALA in WHO grade I lesions is still controversial. A 49-year-old lady was diagnosed in 2004 with a left temporal lobe lesion as an incidental finding; she was followed up clinically and radiologically. In 2016, the lesion showed contrast enhancement and she was offered surgical resection but given she is asymptomatic, she refused. In 2018, the lesion showed signs of transformation with ring contrast enhancement, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Other than the MRI findings mentioned above, the present case could also have been misdiagnosed as a malignant brain tumor based on the following intraoperative findings: (1) the solid component emitted red fluorescence during the intraoperative photodynamic diagnosis, and (2) the results of the rapid intraoperative diagnosis using only one sample from one site indicated a malignant glioma. To the best of our knowledge, only one case of intraoperative fluorescence in PGNT has been reported in the relevant literature (Labrador et al) 10 ; therefore, the former finding was extremely rare. Additionally, Labrador et al reported intraoperative fluorescence in other cases of benign brain tumors.…”
Section: Discussionmentioning
confidence: 90%
“…Other than the MRI findings mentioned above, the present case could also have been misdiagnosed as a malignant brain tumor based on the following intraoperative findings: (1) the solid component emitted red fluorescence during the intraoperative photodynamic diagnosis, and (2) the results of the rapid intraoperative diagnosis using only one sample from one site indicated a malignant glioma. To the best of our knowledge, only one case of intraoperative fluorescence in PGNT has been reported in the relevant literature (Labrador et al) 10 ; therefore, the former finding was extremely rare. Additionally, Labrador et al reported intraoperative fluorescence in other cases of benign brain tumors.…”
Section: Discussionmentioning
confidence: 90%
“…After radical excision, prognosis with free survival and overall survival is very good, with follow-up free of disease for up to 7 years after total resection as reported by Bouvier-Labit et al in their article in 2000 [6,14]. Lavrador et al propose the use of 5-ALA fluorescent in the lesion to achieve complete removal of PGNT [19].…”
Section: Discussionmentioning
confidence: 92%
“…The close association between the ventricular system and the tumors, as was noted in our case, has been commented on by several authors, and it is thought to be due to the possible origin of these tumors from the neuroglial progenitor cells in the subependymal plate as postulated by Komori et al 3 These tumors need to be followed up for a long time since enlargement of the lesion has been reported as late as 10 years after the initial diagnosis. 20,21…”
Section: Discussionmentioning
confidence: 99%